Implementation of the Internal Quality Assurance System at UIN Malang Indonesia - et. al., Mulyono, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the implementation of the internal quality assurance system (IQAS) at the State Islamic University of Maulana Malik Ibrahim Malang Indonesia (called UIN Malang). This research uses qualitative methods, data obtained through interviews, document review and observation, and data analysis techniques using interactive analysis models. The results of the research can be concluded as follows: 1) The University established a Quality Assurance Institute (QAI) at the university level, the Quality Assurance Unit (QAU) at the Faculty level, Postgraduate Program, Language Development Center, and Ma’had (campus dormitories) and Quality Control Groups (QCG) at the Department/Study Program level. 2) Compiling quality assurance system planning in documents: quality policy, quality manual, quality standards, quality forms, monitoring, measurement and self-evaluation, internal quality audits, and Management Review Meetings (MRM). 3) Applying the PDCA (Plan, Do, Check, Action) model which is the application of Total Quality Management (TQM) to produce a cycle of continuous quality improvement. 4) Establish idealized academic service quality standards based on benchmarking results. 5) Ensure the stages of implementation, evaluate and revise quality standards according to benchmarking on an ongoing basis. 6) Establish quality indicators to achieve stakeholder satisfaction, productivity, and efficiency. 7) Internalizing the values ​​and quality culture in the entire campus community. This research produces a strategy for implementing a comprehensive quality assurance system to build UIN Malang as the Center of Excellence and the Center for Islamic Civilization.